APLIKASI MANAJEMEN KASIR PADA KARISMA MEGA SATRIA BERBASIS DESKTOP - Mareanus Lase; Setiya Rini; Feri Prasetyo H; Dewi Yuliandari; Elbiansyah Elbiansyah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract The purpose of this research is to produce a cashier management application at Karisma Mega Satria. The system approach method uses the waterfall method and data collection uses the method of observation, interview and literature study. The design of cashier management development uses Java Netbeans, and MySQL as a database processor. Based on the analysis, it can be concluded that the cashier management application make the sales process easier, able to manage cashier data, sales reports, customer data and support business processes at the Charisma Mega Satria. With the application of cashier management at Karisma Mega Satria can reduce the negligence, errors, accumulation of documents, presentation of reports that are less accurate.